Implementation Of Just In Time (JIT) To Improve Production Efficiency And Reduce Inventory Costs In The Bugis Cake Manufacturing Industry “Toko Serba Oleh-Oleh” - Syerin Annisa Sam; Andri Andri; Mahfud Nurnajamuddin; Suriyanti Suriyanti (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine the implementation of a production system approach focused on cost efficiency at Toko Serba Oleh-Oleh. One of the methods employed is a just-in-time inventory management approach, which seeks to reduce production costs and enhance the effectiveness of raw material management within the company. The researcher utilized a descriptive research technique with a quantitative approach, in which data were collected, processed, and articulated to ensure clarity and ease of understanding. Data collection methods included observation, interviews, and document analysis. The data analysis methodology involved calculating the quantity of raw material orders and total costs based on the company's existing policies, determining the Economic Order Quantity (EOQ) using the EOQ method, assessing the Economic Order Quantity (EOQ) through a JIT/EOQ approach, and evaluating the economic benefits realized as cost savings resulting from the successful implementation of a just-in-time system. The findings of the study indicate that the just-in-time strategy was able to reduce overall inventory costs by 39.12%, with the number of shipments reduced to seven deliveries per order cycle. Raw material procurement occurred three times, with an ideal order quantity of 395 sacks of glutinous rice flour.